The Analysis of Compound Sentence Formation in Moon Jae-In's Posts on Social Media Instagram: An Effort to Increase Writing Skills of Korean Language Education Students UPI - Megasari, Jayanti; Ansas, Velayeti Nurfitriana; Lubis, Arif Husein; Sukyadi, Didi; Restiseptya, Adisty Dyva; Putri, Thrisa Ananda (JLA (Jurnal Lingua Applicata), 2024)
This research is on the formation of compound sentences in Korean, as seen from the uploads on Instagram of former South Korean President Moon Jae-in. On his Instagram, Moon Jae-in uploads photos, videos, and writings containing ideas and responses to things. Researchers see the need to develop writing skills in the Korean Language Education Study Program FPBS UPI. Therefore, the researcher wants to see how Korean speakers form compound sentences according to Korean grammar. As a president, Moon Jae-in is considered able to write in Korean grammar so that it does not cause ambiguity and misunderstanding. The research data found 76 posts by Moon Jae-in and 267 compound sentences. This study also classifies these compound sentences into two classifications, namely 내포문 [nae-pho-mun] 'embedded clause' and 접속문 [jeop-sok-mun] 'conjunctive sentence.' The analysis results show two categories of compound sentence formation patterns in Moon Jae-in's writings: patterns of stacked and non-stacked compound sentence formation. After the analysis was completed, the researcher concluded three strategies for learning to write, namely 1) Students must be able to determine the type of sentence to be made; 2) Students must pay attention to sentence patterns in Korean; and 3) Learners must be careful in choosing the correct grammar.